Liberative solidarity : contemporary perspectives on mission - Abraham, K. C (Tiruvalla Christava Sahitya Samithi, 1996)
Traditional patterns of mission fail to meet the emerging needs and challenges of the Third World-endemic poverty, marginalisation, ecological destruction, globalisation, etc.....Proposals for new paradigms to do theology and to formulate its response in mission in the face of these grave realities are clearly spelt out in this book. Two themes that run through these theological and missiological reflections are "Life" and "Solidarity". Our commitment to life affirming values and structures are integral to our obedience to Christ, who lived in solidarity with the oppressed humanity. This conviction emerges from the faith of the author, his commitment to the poor and the marginalised. The author is, as Dr. James H. Cone notes in his foreword of this book, "uniquely qualified to write about the new developments in mission, ecology, theology and their interconnectedness." (Back cover).
Keywords: Mission of the church. Church renewal